2002
DOI: 10.1177/1357633x020080s247
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Access to Their Online Electronic Health Records

Abstract: We surveyed a randomized group of 1050 adult patients stratified for age and sex, from a general practice in Oxfordshire, to find out their attitudes to electronic health records (EHRs). Eighty-six per cent thought that patients should have the right to see their records. While 72% knew that they had the right to see their records, only 4% had done so. Private EHR viewing booths with a computer and fingerprint identification system were installed in the primary care centre. Patients were randomly selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…The most frequent types of technology covered were: electronic health records (EHR) (n = 23 studies) [39,40,42,45,47,49,54-59,62,65-68,70,72,75-77,79,81,90,92]; electronic medical records (EMR) (n = 19) [35,43,44,46,48,51,52,60,61,64,69,71,73,74,78,82,83,86,88]; electronic patient records (EPR) (n = 5) [50,53,87,91,93] and computer-based/computerized patient records (n = 2) [36,63]. Other forms of technology were each represented by one study: computerized patient information system [80], computerized medical records [84], electronic records management [34], personal health records [38], portable computers [89], smart card [85], and summary care records [37,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent types of technology covered were: electronic health records (EHR) (n = 23 studies) [39,40,42,45,47,49,54-59,62,65-68,70,72,75-77,79,81,90,92]; electronic medical records (EMR) (n = 19) [35,43,44,46,48,51,52,60,61,64,69,71,73,74,78,82,83,86,88]; electronic patient records (EPR) (n = 5) [50,53,87,91,93] and computer-based/computerized patient records (n = 2) [36,63]. Other forms of technology were each represented by one study: computerized patient information system [80], computerized medical records [84], electronic records management [34], personal health records [38], portable computers [89], smart card [85], and summary care records [37,41].…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies (n = 17, 32.7%) were conducted in European countries: United Kingdom (n = 10) [37,41,53,58,67,68,72,79,81,90], Norway (n = 5) [46,50,60,87,88], Sweden (n = 3) [36,51,52], Denmark (n = 3) [75,91,93], Greece (n = 1) [49] and Spain (n = 1) [74]. Two Australian (3.8%) [80,84] and two Japanese studies [43,44] were also included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Experience, literature reviews and research suggest that RA in general practice improves safety, 14 patient satisfaction 15 and compliance with treatment. 2,16 This may come from a greater sense of understanding and control felt by patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 This low uptake could be due to a general lack of interest, fears about the complexity of the information, or simply a lack of awareness of their right to do so. 2,3 Doctors too, as a group, have not generally encouraged patients to examine what is written about them clinically. Previous research suggests that clinicians have concerns for the potentially negative impacts of allowing patients access to their records, fearing that patients might misinterpret the material or that it might undermine self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…3 The aim of the research reported in this paper was to investigate the attitude of patients attending a London-based primary care practice to having access to their electronic records, their perception of how it would alter the sense they made about their health, the impact on the doctor-patient relationship, and patients' interest in being permitted to add to the notes themselves.…”
Section: Introductionmentioning
confidence: 99%